WEBSITE AS AN COMMUNICATION TOOL AND BRANDING STRATEGY IN TELECOMMUNICATION COMPANIES: - - Erni Martini; Lili Adi Wibowo; Agus Rahayu; Ratih Hurriyati (Jurnal Manajemen dan Kewirausahaan, 2022)
This research had the purpose of investigating the utilization of a company's official website as a communication medium and for online branding purposes in the telecommunication industry in Indonesia. This study used a population of official websites from seven telecommunication companies in Indonesia. The indicators that had been used to analyze website content, website ease of use, and website interactivity. The results of this study showed that 100% of telecommunication companies in Indonesia had a website that can be used as an online branding strategy. The indicators that were mostly used by these companies for online branding were website content (100%) and website ease of use (93.65%), while the use of website interactivity (53%) still needed to be maximized. The findings of this study were useful in revealing how telecommunications companies in developing countries used their websites as a communication medium for online branding